Visible light-initiated living cationic dark polymerization. Issue 47 (16th November 2022) - Wang, Lei; Huang, Pei; Huang, Lei; Chen, Chuanshuang; Qi, Meiwei; Jiang, Wenfeng; Yu, Chunyang; Zhang, Shaodong; Zhou, Yongfeng
Abstract : A metal-free, visible light-initiated living cationic dark polymerization system using tris(4-methoxyphenyl)methyl tetrafluoroborate as the photocatalyst and methanol as the chain transfer agent (CTA) is demonstrated. Abstract : Visible light-controlled living cationic polymerization systems reported so far rely on continuous irradiation to maintain the propagation process. This technique can achieve spatial and temporal control, but its energy consumption is inefficient and will have light penetration issues during the polymerization. Herein, a metal-free, visible light-initiated living cationic dark polymerization system using tris(4-methoxyphenyl)methyl tetrafluoroborate as the photocatalyst and methanol as the chain transfer agent (CTA) is demonstrated. It exhibits remarkable living characteristics, such as first-order kinetic behaviour, controlled molecular weight, narrow dispersity, and long-lived polymer chains, during the dark polymerization process following the light-initiation stage. This new living polymerization system has the advantages of spatio-temporal controlled initiation, energy saving process and high-penetration polymerization, and has potential for industrial applications.